The Brazilian Association for Educational Evaluation - José Francisco Soares (Universidad Autónoma de Madrid, 2018)
In the 1990s, Brazil achieved its children and adolescents from 7 to 14 years of age at elementary school. Although this occurred long after some countries in Latin America, this is an important fact for a country with continental dimensions and a history of much social inequality